(untitled) (Libellarium: časopis za istraživanja u području informacijskih i srodnih znanosti, 2017)
This issue of Libellarium fetaures papers based on the presentations from the 14th international conference Libraries In the Digital Age (LIDA) which took place in Zadar, Croatia, on June 13-17 2016. All papers were subject to evaluation and classification by two independent reviewers, according to the journal’s editorial policy. The conference gathered 134 participants from 22 countries (Austria, Belgium, Brasil, Denmark, France, Croatia, Irland, Italy, Jamaica, Japan, South African Republic, Canada, Germany, Hungary, Netherlands, USA, Singapore, Slovenia, Switzerland, Taiwan, Thailand and Great Britain. The papers published in this volume concentrate on three main conference topics: education of information professionals, digital curation and user studies. The first part features three papers. Tatjana Aparac-Jelušić in Education for digital libraries: A European perspective addresses the trends in the European Higher Education Space which influence the education in information sciences. Vera Hillebrand and Elke Greifeneder (International mobility in Library and Information Science) present the results of the quantitative study that examined whether a brain drain exists in LIS and explored the patterns of geographical mobility of researchers. Interestingly, the study revealed two alarming trends: the American LIS researchers rarely ever leave their continent and might lack international exposure. On the other hand, researchers from Asia and Europe show a high rate of mobility towards North America. In Understanding roles and responsibilities of data curators: An international perspective Anna Maria Tammaro, Krystyna Matusiak, Frank Andreas Sposito, Vittore Casarosa and Ana Pervan present the preliminary findings of a large research project whose primary objective is to identify the tasks and responsibilities of data curators and ultimately to develop a “data curation ontology” that will better define the profession and support the development of educational curricula to train future data curators. In the section two authors focus on digital curation and related topics. Patricia Aufderheide (Leveraging exceptions and limitations for digital curation and online collections: The U.S. Case) discusess the utility of the major exception to copyright monopoly rights, fair use, and addresses the efforts of the Association of Research Libraries to clarify how it can be employed by libraries. In Social science research data curation: Issues of reuse Guangyuan Sun and Christopher Soo Guan Khoo discuss the issues of reusing quantitative social science data from three perspectives of searching and browsing for datasets, evaluating the reusability of datasets, and integrating datasets, by comparing dataset searching with online database searching. Tove Faber Frandsen and Jeppe Nicolaisen (Statistical analyses of digital collections: Using a large corpus of systematic reviews to study non-citations) indicate that the use of statistical methods to analyse digital material for patterns makes it possible to detect patterns in big data that we would otherwise not be able to detect and they try to exemplify that fact by statistically analysing a large corpus of references in systematic reviews. Frances Salmon, Maureen Kerr-Campbell and Paulette A. Kerr in Managing a digital archiving project at the University of the West Indies Library: A case study address the strategies employed by a team at the University of the West Indies, Mona Library, including the acquisition of equipment, selection of collections to be included, and digitization of thirty collections of varied formats as well as deliberate collaborative initiatives at training of staff to ensure sustainability. They also discusses challenges, such as legal issues, politics, ownership, and values involved in stewardship of the collections. Milijana Mičunović, Hana Marčetić and Maja Krtalić in Data organization and preservation in the context of digital and networked media: public’s attitudes, habits and practices in relation to digital curation of personal digital data present the results of their small scale survey which was driven by the following research questions: What are the attitudes of working population towards organizing and safekeeping digital documents that they create in everyday life? To what extent is personal digital archiving among working population a planned activity or just a side-effect of generating content in the digital environment? How do they organize and preserve digital data and documents, both offline and online? What are their attitudes to digital afterlife and digital legacy? In Scholarly reference trees Kristina Kocijan, Marko Požega and Dario Poljak propose, explain and implement bibliometric data analysis and visualization model in a web environment. Ya-Ning Chen (An Analysis of Characteristics and Structures Embedded in Data Papers: A Preliminary Study) presents the results of the study that aimed to build up a common structural framework to investigate the embedded characteristics and structures of the content of data papers by using a content analysis approach. In their paper Dina Mašina and Kristijan Crnković present new modules of the Digital repository of Croatian Academy of Sciences and Arts. A number of papers focus on user experience in digital libraries. Marton Nemeth in Semantic web developments in Hungarian public collections in an international perspective describes international context of Hungarian semantic web projects. Nicolas Prongué, Fabio Ricci, René Schneider and René Schurte present results of the project LODZ (Linked Open Data Zurich). The aim of the project was to merge data from three institutions in the field of art and design and develop a semantic web infrastructure to enable data discovery. Based on the results of his study that used historical and content analysis, Mirko Duić (How to build better participative digital libraries and their user communities – Insights from the user study of the Facebook heritage group „Zagreb as it used to be”) proposes guidelines for better communication between creators of digital collections and users. Problems of digital preservation are addresses by Roman Graf, Sergiu Gordea, Heather M. Ryan and Tibaut Houzanme in An expert system for facilitating an institutional risk profile definition for cyber situational ewareness. The authors present a method to facilitate decision-making for the preservation of digital content in libraries and archives using institutional risk profiles that highlight endangered files formats (in danger of becoming inaccessible or unusable). Bilingual and trilingual thesauri of Croatian language are studied by Tihomir Živić, Marina Vinaj and Dina Koprolčec (Digitization of Older Croatian Dictionaries: A Possible Substratum for Terminological Neologisms?) through the prism of digitization. Authors believe that such studies can help understand what happens with Croatian language, especially in relation to the large number of foreign words. Language-related topic is addressed by Vlatka Ivić and Tomislav Jakopec as well. In Using mobile application in foreign language learning: a case study they present the mobile application FFOS Test Your Knowledge (FFOS TYK) that aims to provide additional foreign language training for students on multiple platforms. Three papers deal with information literacy and human information behaviour. Results of the study into the level of information literacy of student beginners were described by Angela Maurer, Christian Schlögl and Stefan Dreisiebner (Comparing information literacy of student beginners among different branches of study). Alica Kolarić and Ivanka Stričević in Information seeking behavior for decision making in everyday life: A pilot study on adolescents) describe the study that aims to reveal whether adolescents engage in deliberate information seeking when facing everyday life decisions and if so, which information sources they use. Moreover, the research explores the importance attached by adolescents to information in making decisions. Ivana Turk and Kornelija Petr Balog (Information horizons of Croatian professionals in education and medicine) present the results of the study that aimed to identify the categories of information sources used by physicians and teachers of Croatian language in work-related situations. And finally, Tjaša Jug and Maja Žumer (Do we need better online book review organisation?) describe the results of their study that analysed Amazon customer reviews. They were interested in the aspects of a book users perceive as important and the extent to which these attributes match FRBR entities. The also studied the relation between specific attributes in the reviews and the numeric rating of the book. Papers published in this volume of Libellarium address different aspects of the conference’s main theme (Digital library curation and collections) and contribute to the discussion and understanding of these important phenomena and developments at the international level.